The Effect of Return on Assets, Earnings Per Share, Cash Conversion Cyle, Price Book Value and Gross Profit Margin on Stock Returns in Food and Drink Companies Listed on The Indonesia Stock Exchange In 2017-2019 Period - Mas Intan Purba; Irna S.V Manalu; Cahaya Romian Lubis; Bryan Maradika Sembiring; Ananda Latersia Sembiring (Budapest International Research and Critics University, 2022)
This study aims to explain the effect of Return on Assets, Earning Per Share, Cash Conversion Cyle, Price Book Value and Gross Profit Margin on Stock Return. The population of this study were 38 companies in the Food and Beverage sub-sector and only 13 companies that met the criteria using the Purposive Sampling technique. This study uses secondary data with classical assumption test and multiple regression analysis. The results showed that simultaneously Return on Assets, Earning Per Share, Cash Conversion Cyle, Price Book Value and Gross Profit Margin had a significant and significant effect on Stock Return. Cash Conversion Cyle partially and significantly affects Stock Return. while partially Return on Assets, Earning Per Share, Saham in food and beverage companies. Coefficient of Determination Value (R2) R Square value of 0.280 with a rate of 28 percent. So, the effect of Return on Assets, Earning Per Share, Cash Conversion Cyle, Price Book Value and Gross Profit Margin on Stock Return is 28 percent. The remaining 72 percent is influenced by other variables not examined in this study.